Prognostic influence of mechanical cardiopulmonary resuscitation on survival in patients with out-of-hospital cardiac arrest undergoing ECPR on VA-ECMO - Springer, A.; Dreher, A.; Reimers, J.; Kaiser, L.; Bahlmann, E.; van der Schalk, H.; Wohlmuth, P.; Gessler, N.; Hassan, K.; Wietz, J.; Bein, B.; Spangenberg, T.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction The use of venoarterial extracorporeal membrane oxygenation (VA-ECMO) in extracorporeal cardiopulmonary resuscitation (ECPR) in selected patients after out-of-hospital cardiac arrest (OHCA) is an established method if return of spontaneous circulation cannot be achieved. Automated chest compression devices (ACCD) facilitate transportation of patients under ongoing CPR and might improve outcome. We thus sought to evaluate prognostic influence of mechanical CPR using ACCD in patients presenting with OHCA treated with ECPR including VA-ECMO. Methods We retrospectively analyzed data of 171 consecutive patients treated for OHCA using ECPR in our cardiac arrest center from the years 2016 to 2022. A Cox proportional hazards model was used to identify characteristics related with survival. Results Of the 171 analyzed patients (84% male, mean age 56 years), 12% survived the initial hospitalization with favorable neurological outcome. The primary reason for OHCA was an acute coronary event (72%) followed by primary arrhythmia (9%) and non-ischemic cardiogenic shock (6.7%). In most cases, the collapse was witnessed (83%) and bystander CPR was performed (83%). The median time from collapse to VA-ECMO was 81 min (Q1: 69 min, Q3: 98 min). No survival benefit was seen for patients resuscitated using ACCD. Patients in whom an ACCD was used presented with overall longer times from collapse to ECMO than those who were resuscitated manually [83 min (Q1: 70 min, Q3: 98 min) vs. 69 min (Q1: 57 min, Q3: 84 min), p = 0.004]. Conclusion No overall survival benefit of the use of ACCD before ECPR is established was found, possibly due to longer overall CPR duration. This may arguably be because of the limited availability of ACCD in pre-clinical paramedic service at the time of observation. Increasing the availability of these devices might thus improve treatment of OHCA, presumably by providing efficient CPR during transportation and transfer.